The Construction of Ithbat-bila-Kayf Theology: An Analysis of Imam Bukhari’s Theological Methodology in the Book Khalq Af’al al-Ibad - M. Dede Rodliyana; M. Rachmatullah Arken (Diroyah : Jurnal Studi Ilmu Hadis, 2026)
This study seeks to examine the theological thought of Imam al-Bukhari in his work, Khalq Af’āl al-’Ibād, amidst the escalation of theological conflicts in the 3rd century AH. The primary focus of this study is to map out the Ithbāt bilā Kayf methodology advocated by al-Bukhārī as a response to the Ta’ṭīl (denial of attributes) doctrine of the Jahmiyyah and the threat of anthropomorphism (tashbīh). This study employs a qualitative method through a descriptive-analytical approach and the technique of content analysis (content analysis). This study found that al-Bukhārī constructs a precise theological argument by distinguishing between the actions of servants (af’āl al-’ibād) as created beings and the Qur’an as Kalamullāh, which is not created. The results of the study indicate that al-Bukhārī systematically organised the traditions of the Salaf to affirm the attributes of Allah, including the attributes of Istiwa’, Knowledge, and Voice (Ṣawt), without engaging in anthropomorphism. This study concludes that al-Bukhārī’s theological framework constitutes a model of “Textual Kalam” which forms the foundation of moderate Sunni orthodoxy (wasaṭiyyah), successfully harmonising submission to the text of revelation with the recognition of the reality of creation